894. Patient and Surgery Characteristics on Wound Complication and Surgical Site Infection in Sarcoma Patients undergoing Hemipelvectomy. (31st December 2020) - Katzman, Ju Hee; Sun, Steven; Joyce, David; Greene, John
Abstract: Background: Hemipelvectomy is associated with a significant risk of wound complications, including infections, bleeding and injuries to nearby neurovascular structures as well as the gastrointestinal and genitourinary tract. This study aimed to determine the patient characteristics and approach to treatment that could affect the occurrence of surgical site infection or wound complications in sarcoma patients undergone hemipelvectomy. Methods: We conducted a retrospective analysis of 33 adult patients who underwent hemipelvectomy at Moffitt Cancer Center, Tampa, FL, from 2008 to 2016. We used Chi-square (Exact Fisher) test to investigate the association between wound complication and categorical variables. We used a T-test to evaluate the difference in numerical variables for outcomes. Results: Out of 33 patients, 12 (36.4%) patients experienced wound complications after hemipelvectomy (Table 1). The average age of patients with wound complications was 63.3 3 (57.1±15.4) years old, significantly higher than that of patients without wound complications (p=0.004). Without adjustment, the use of computer navigation had a lower wound complication rate (p=0.027). Patients with wound complications had longer hospital length of stay (14.8 vs. 7.0 days, p=0.016). Among patients with surgical site infection (Table 2), there were no patients' characteristics or surgical characteristics associated with this outcome. Five (15%) patients developed surgical site infection and they had longer hospital stay (19.4 vs. 8.1 days, p=0.001). The organisms identified from wound cultures include methicillin-resistant Staphylococcus aureus, viridans Streptococcus, Peptostreptococcus asaccharolyticus, Enterobacter cloacae, Pseudomonas aeruginosa, Candida albicans . The organisms in late infections (more than 6 months since surgery), included above organisms plus Stenotrophomonas maltophilia and Achromobacter xylosidans . Conclusion: Older patients undergoing hemipelvectomy are at an increased risk of developing wound complications with a prolonged hospital stay. Initial antimicrobial therapy for suspected surgical site infection should include a broad-spectrum coverage to include skin and gastrointestinal flora. Disclosures: All Authors : No reported disclosures